2023
DOI: 10.1177/10983007231200529
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fidget Toys on Story Detail Acquisition and Visual Attention for Elementary Students With Autism

Kathleen N. Zimmerman,
Jennifer R. Ledford,
Virginia R. Turner

Abstract: Fidget toys are recommended as “sensory” tools to improve the attention and performance of elementary students with autism. The purpose of this study was to evaluate how fidget toys affected the visual attention and skill acquisition of elementary students with autism during storybook reading. Provision of fidget toys was compared with a no-fidget baseline using two separate, concurrent single-case research designs. The provision of fidget toys resulted in a decrease in visual attention for some, but not all, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Other studies have found that a fidget toy in the classroom has either no effect or negative effects on on-task behaviour (Croley et al, 2022;Zimmerman et al, 2023). They found that while there were fewer neighbouring distractions, tasks were still not being completed (Croley et al, 2022).…”
Section: Background Research: Fidgetsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies have found that a fidget toy in the classroom has either no effect or negative effects on on-task behaviour (Croley et al, 2022;Zimmerman et al, 2023). They found that while there were fewer neighbouring distractions, tasks were still not being completed (Croley et al, 2022).…”
Section: Background Research: Fidgetsmentioning
confidence: 96%
“…Fidget toys are often used as a sensory intervention to aid in self-regulation and attention (Aspiranti & Hulac, 2021;Croley et al, 2022;Kriescher et al, 2023;Zimmerman et al, 2023). There are currently limited studies on fidget toy use for meeting sensory needs.…”
Section: Background Research: Fidgetsmentioning
confidence: 99%